Development of background identifying tool in the BASF2 - Manish (IISER Mohali, 2023)
Identifying the possible source of background is important for any high energy physics analysis. So we present a utility to tag and identify the MC decays using there the generator level information. One can simply use some BASF2 variables to separate out the signal and different sources of the background.
Keywords: belle II Detector; BASF2 tool